Krypton Diffusion in UO2 Assuming a Strong Bonding Krypton-Oxygen. A Molecular Dynamics Simulation - Seitov, D.D.; Nekrasov, K.A.; Kupryazhkin, A.Ya. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
a molecular dynamic simulation of Kr bulk diffusion in UO2 isolated nanocrystals is conducted in the assumption of a strong krypton-oxygen bonding. Thecrystals consisted of 5460 ions.The modeling carried out by parallelizing the computations on the graphics processing units of the CUDA architectures GK110 and GP102 using the NVIDIA GeForce GTX 780Ti and 1080Ti video cards. The frequencies of the diffusion jumps and the values of the diffusion coefficient are calculated at temperatures from 2325 K to 2800 K. The interstices surrounded by the eight closest oxygen neighbors are shown to be the equilibrium positions of the krypton atom. The main observed migration mechanism is movement of the atom between the interstitial positions via the anionic vacancies. The values of the diffusion coefficient are from 5 · 10 −7 to 2 · 10 −5 , and the diffusion activation energy is E D = (4.8 ± 0.3) eV.